On the event. A contemporary outlook to the city (2011)
The article presents a meditation about the city as place for the event. Beginning from the relationship between art and the city the author points out that art do not represent the city but becomes an extension of it (Argan, 1986), while its architecture constitutes the matter: the materialization of its ever-changing ocean of timelessness. Urban spaces procure and foment actions, but the space does not precede the action: it is the outcome; and the event, as an atural flux, is akin to fractal geometries and chaotic dynamic systems. The urban dweller, hence, is rooted in the permanent change, the ephemeral, the event, the human acting. Historically, it is evident that places transcend time due to the symbolic signifiers associated to them despite its physical appearance, therefore, a definition ofthe event should consider two relative tenses: the timelessness of the object and the temporality of the human. As a conclusion, the article stretches that a project for the city of today must be inconjunction with the place, but mostly with the event: it must take into account the foreseen of the facts and the unforeseen of the action; it must allow for guidelines, but not conditioning; it must be open to modifications and change.